2019
DOI: 10.24198/pjd.vol31no2.18540
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of namnam (Cynometra cauliflora L.) leaves extract on the growth of Porphyromonas gingivalis

Abstract: Introduction: Porphyromonas gingivalis growth should be prevented to minimise inflammation in periodontal tissues. Antibacterial herbs need to be considered because there are side effects caused by synthetic antibacterial drugs. Namnam (Cynometra cauliflora L.) leaves are known for having antibacterial effects. The purpose of this research was analysing the inhibition potential, and the highest inhibition concentration of namnam leaves extract on the growth of Porphyromonas gingivalis. Methods: 24 samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A methanol leaf extract showed significant antioxidant [15,60,62,63]; antibacterial (against Staphylococcus aureus, Escherichia coli, Porphyromonas gingivalis, and methicillinresistant Staphylococcus aureus [33,62,67]); anti-viral (against herpes simplex virus type 1) [71]; anti-diabetic; antidiarrheal (in vivo) [63]; and cytotoxic potentiality against brine shrimp (Artemia salina) and Vero cells [71,72]. An ethanol leaf extract showed anti-inflammatory activity by inhibiting the activities of arachidonate-5-lipoxygenase and hyaluronidase [64].…”
Section: Biological Studiesmentioning
confidence: 99%
“…A methanol leaf extract showed significant antioxidant [15,60,62,63]; antibacterial (against Staphylococcus aureus, Escherichia coli, Porphyromonas gingivalis, and methicillinresistant Staphylococcus aureus [33,62,67]); anti-viral (against herpes simplex virus type 1) [71]; anti-diabetic; antidiarrheal (in vivo) [63]; and cytotoxic potentiality against brine shrimp (Artemia salina) and Vero cells [71,72]. An ethanol leaf extract showed anti-inflammatory activity by inhibiting the activities of arachidonate-5-lipoxygenase and hyaluronidase [64].…”
Section: Biological Studiesmentioning
confidence: 99%
“…22 Gingipain functions to degrade fibrinogen and heme host proteins, which inhibit blood clotting so that bleeding worsens. 6 When the protease or gingipain enzymes are inhibited, the bacteria lose their source nutrition and decreased function, such as difficulty adhering to target cells and cell death. 23 Flavonoids can also increase the secretion of inflammatory cytokines such as interleukin 1β, interleukin 6, interleukin 8, and tumour necrosis factor or TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…5 Virulence factors such as lipopolysaccharide (LPS), fimbriae, protease, capsule, adhesive domain, and outer membrane vesicle owned by P. gingivalis can invade local periodontal tissues, take nutrients for growth, and defend themselves from the body's defence mechanisms. 5,6 These pathogenic bacteria appear as much as 85.75% in the sample subgingival plaque in patients with chronic periodontitis, and about 40-100% of adults with chronic periodontitis are infected by these opportunistic bacteria.⁶ Several classes of antibiotics are recommended to treat chronic periodontitis, such as clindamycin, doxycycline, amoxicillin, and metronidazole. 7 Improper administration of antibiotics can lead to antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory zone diameters of each sample interpreted based on Davis & Stout (1971) criteria, where the diameter of the inhibitory zone divided into three categories: 1) weak, if the diameter of the inhibitory zone of less than 10 mm, 2) moderate, if the diameter of the inhibitory zone 10-20 mm and 3) Strong, if the diameter of the inhibitory zone of more than 20 mm. 10 According to Table 1, the result showed that the ethanol extract Pluchea indica (L.) Less leaves had moderate-strong antibacterial activity towards S. mutans, P. gingivalis dan E. faecalis bacteria. Strong antibacterial activity is only found at concentrations of 5.5% and 6.5% against S. mutans and E. Faecalis bacteria, and the other concentrations have moderate activity.…”
Section: Discussionmentioning
confidence: 99%